The Role of the Tanya Nami Hakhi Baraita - Goldsmith, Simcha (Hebrew Union College annual, 2002)
The technical term תניא נמי הכי is used in the Babylonian Talmud to introduce a baraita that follows a memra. The similar and oftentimes identical language of the memra and baraita raises the question: If there was an extant baraita, why did the amora not quote it? Traditional responses and most modern scholars suggest that the amoraim were not familiar with all of the baraitot. This paper first critiques J.Hauptman's theory that baraitot formed the sugya's earliest redacted stratum, and J.Frenkel's suggestion that memrot, unknown to the amoraim, were really baraitot that preceded the redaction of the Mishnah. In order to clarify the role of the TNH baraita, this paper will analyze other types of sugyot in both Talmuds in which baraitot follow memrot. The evidence suggests that the amoraim's knowledge of the vast tannaitic literature was more comprehensive than assumed by traditional and modern scholars. The amoraim freely quoted baraitot without citing their tannaitic origin and in some instances quoted only relevant sections and not the entire baraita. This gave the false impression that the amoraim were not familiar with the baraitot. TNH baraitot were inserted into sugyot at a later date in order to corroborate the memrot or to footnote the tannaitic origin of the memra.